Representation of Africa in post-colonial Anglophone writings: V. S. Naipaul, Chinua Achebe and J. M. Coetzee - Chowdhury, Md. Shafiul Alam Khan (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2014.